Against the impairment argument: A reply to Hendricks. (3rd February 2020) - Räsänen, Joona
Abstract: In an article of this journal, Perry Hendricks makes a novel argument for the immorality of abortion. According to his impairment argument, abortion is immoral because: (a) it is wrong to impair a fetus to the nth degree, such as causing the fetus to have fetal alcohol syndrome (FAS); (b) it is wrong to impair a fetus to the n +1 degree (to cause the fetus to be more impaired than to have FAS); (c) killing the fetus impairs the fetus to the n +1 degree (causes it to be more impaired than to have FAS); (d) abortion kills the fetus; (e) therefore, abortion is immoral. The impairment argument is a promising account for the wrongness of abortion because it does not rely on the controversial metaphysical premise that a fetus is a person. This article aims to show, that despite some immediate advantages over the rival theories of the immorality of abortion there is a reason to believe that the impairment argument is untenable. That is because there are goods that can be achieved by abortion but that cannot be achieved by impairing the fetus.